2021
DOI: 10.1007/s11367-021-01908-y
|View full text |Cite|
|
Sign up to set email alerts
|

Characterizing antibiotics in LCA—a review of current practices and proposed novel approaches for including resistance

Abstract: Purpose With antibiotic resistance (ABR) portrayed as an increasing burden to human health, this study reviews how and to what extent toxicological impacts from antibiotic use are included in LCAs and supplement this with two novel approaches to include ABR, a consequence of antibiotic use, into the LCA framework. Methods We review available LCA studies that deal with toxicological aspects of antibiotics to evaluate how these impacts from antibiotics have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Specifically, amoxicillin presented an effect more than 30,000 times greater than ampicillin, so in case of doubt between the application of one or the other, the antibiotic ampicillin is recommended from the point of view of FE. Nyberg also confirmed this effect (Nyberg et al, 2021), in their freshwater ecotoxicity studies they found that of the 40 antibiotics studied, amoxicillin had the most negative effects on freshwater ecotoxicity Amoxicillin is expected to pose adverse effects for cyanobacteria, suggesting potential ecological risks, whereas ibuprofen pose a small potential for adverse effects to invertebrates and fish, respectively (Gómez-Canela et al, 2019;Kovalakova et al, 2020).…”
Section: Simulation Of the Toxicity Impact Of Apis In Hospital Effluentsmentioning
confidence: 79%
See 1 more Smart Citation
“…Specifically, amoxicillin presented an effect more than 30,000 times greater than ampicillin, so in case of doubt between the application of one or the other, the antibiotic ampicillin is recommended from the point of view of FE. Nyberg also confirmed this effect (Nyberg et al, 2021), in their freshwater ecotoxicity studies they found that of the 40 antibiotics studied, amoxicillin had the most negative effects on freshwater ecotoxicity Amoxicillin is expected to pose adverse effects for cyanobacteria, suggesting potential ecological risks, whereas ibuprofen pose a small potential for adverse effects to invertebrates and fish, respectively (Gómez-Canela et al, 2019;Kovalakova et al, 2020).…”
Section: Simulation Of the Toxicity Impact Of Apis In Hospital Effluentsmentioning
confidence: 79%
“…The endpoint methods are applied to the indicator to express the current damages while the mid-point methods are applied to the characterization factor in order to measure the impact (Fernández-Marchante et al, 2021;Nyberg et al, 2021). The ReCiPe mid-point method includes the following impact categories: particulate matter formation, ozone formation (human health), ionizing radiation, stratospheric ozone depletion, human toxicity (cancer), human toxicity (non-cancer), global warming, water use, freshwater ecotoxicity, freshwater eutrophication, ozone formation (terrestrial ecosystems), terrestrial ecotoxicity, terrestrial acidification, land use, marine ecotoxicity, mineral resource depletion and fossil energy consumption (Su et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The results from this approach are pretty similar to those obtained previously by C‐PCR. However, to get high sensitivity, two‐step PCR is necessary, which is expensive and time‐consuming (Nyberg et al, 2021).…”
Section: Rapid Genomic Detectionmentioning
confidence: 99%
“…So far, established life cycle impact assessment methods and models have not accounted for the development and spread of AMR due to antibiotic emissions into the environment. Nyberg et al (2021) recently proposed a novel approach to characterize the potential for AMR enrichment in the environment as a midpoint indicator, and another conceptual approach to directly link the total use of antibiotics in a given region to human health impacts at the endpoint damage level (DALY/kg antibiotic used). Similarly, Emara et al (2021) derive minimum selective concentrations from widely available antibiotic susceptibility data and determine hazardous concentrations (HCs) for more than 140 antibiotics that reflect an antibiotic-specific threshold for resistance selection in the environment.…”
Section: Recommendations and Further Research Needsmentioning
confidence: 99%